Rotavirus genotypes as etiological agents of diarrhoea in general populations of two geographic regions of Brazil - Leite, Marcel (2017)
Rotavirus is the main global cause of severe childhood diarrhoea among children. In 2006, Rotarix® (G1P[8]) was introduced into Brazil’s National Immunization Program. The vaccine coverage rate was 84.4% in 2009. Evidences of increasing G2P[4] after 2006 opened up the discussion about the vaccine effectiveness to non-G1 strains. The aim of this study was to identify the circulating rotavirus genotypes in two Brazilian regions during 2009. A total of 223 positive samples by immunochromatography and latex agglutination assay from the Northeast (Bahia/Pernambuco States) and Southeast (São Paulo/Rio de Janeiro States) regions were included in the study. The samples were submitted to genotyping by nested-PCR according to VP7(G) and VP4(P) and 175 samples (78.5%) were able to be characterized. Considering the characterization of VP7, the G-types detected were G1, G2, and G4 in the Northeast, and G2, G3, G5, and G9 in the Southeast. Considering the characterization of VP4, the P-types detected were P[4], P[8], and P[6]/P[9] in the Northeast and the Southeast. The most frequent mixed types found were G2P[4]/G2P[NT](81.4%), G2P[6](5.2%), G1P[6](5.2%) in the Northeast, and G2P[4]/G2P[NT](78.8%), G2P[6](8.2%), G9P[8](4.7%) in the Southeast. Among immunized individuals whose age ranged from 0-4 years, the G2P[4]/G2P[NT] genotype was identified in 91,0% of cases, and among non-immunized individuals of the same age, the G2P[4]/G2P[NT] genotype was identified in 85.7% of the cases. In accordance with the high level of vaccine coverage, the data suggest that the circulation of G2P[4] in these regions had a considerable increase after the introduction of Rotarix®.